Engaging Youth in Farming is Key to the Future Food Security in Bangladesh - Haque, Abdul; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2025)
Bangladesh's economy heavily relies on agriculture, with a significant portion of the population dependent on agricultural activities, both directly and indirectly. Agriculture contributes approximately 11% to the country's GDP and is crucial to employment generation and food security. However, the agricultural sector faces challenges due to climate change, rapid population growth, and the conversion of agricultural land for unplanned development. These factors are increasing pressure on food security.